1999
DOI: 10.1103/physrevb.59.11502
|View full text |Cite
|
Sign up to set email alerts
|

Phase dependence of the Josephson current in inhomogeneous high-Tcgrain-boundary junctions

Abstract: We present an experimental and theoretical study of the current-phase relation I s () for 45°grain boundaries in YBa 2 Cu 3 O 7Ϫx films. A model of strongly inhomogeneous Josephson junctions, in which the presence of randomly alternating current leads to a deviation of I s () from the well-known sin() dependence, has been used. This deviation decreases with the temperature T and is described by the formula I s ()ϭI c (T)(sin ϩ␥(T)sin2). Using the developed model, the coefficient ␥ is calculated and its tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Thus, for very thin barriers, equation (1) is equivalent to the assumption that an integral of the potential barrier height taken along an electron path inside the classically forbidden region is a uniform random variable (note that in a strongly disordered insulating layer such a path can significantly exceed the nominal barrier thickness d due to elastic subbarrier defect scatterings). Even more, we can conclude that the Schep-Bauer formula (1) for the transparency D is not limited to this assumption but is valid, independently of the physical nature, when (i) the transparency may be represented as a one-parameter Lorentzian and (ii) this parameter is uniformly distributed from very small up to very large values (see the related discussion concerning spatial distribution of barrier defects in the paper by Il'ichev et al [36]). It is interesting that before the work [6], the same relation (1) was derived for a quasi-ballistic double-barrier INI interspace with two identical uniform insulating layers [37], a system that is physically very different from a thin disordered dielectric film.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, for very thin barriers, equation (1) is equivalent to the assumption that an integral of the potential barrier height taken along an electron path inside the classically forbidden region is a uniform random variable (note that in a strongly disordered insulating layer such a path can significantly exceed the nominal barrier thickness d due to elastic subbarrier defect scatterings). Even more, we can conclude that the Schep-Bauer formula (1) for the transparency D is not limited to this assumption but is valid, independently of the physical nature, when (i) the transparency may be represented as a one-parameter Lorentzian and (ii) this parameter is uniformly distributed from very small up to very large values (see the related discussion concerning spatial distribution of barrier defects in the paper by Il'ichev et al [36]). It is interesting that before the work [6], the same relation (1) was derived for a quasi-ballistic double-barrier INI interspace with two identical uniform insulating layers [37], a system that is physically very different from a thin disordered dielectric film.…”
Section: Discussionmentioning
confidence: 92%
“…We have argued that its presence originates from a very broad and homogeneous distribution of local barrier heights generated by oxygen vacancies within the aluminum oxide film. If the defect distribution is more or less uniform [36], the integral of the potential barrier height along an electron path inside the barrier would be a uniform random variable. Of course, this phenomenon is not scale invariant.…”
Section: Discussionmentioning
confidence: 99%
“…31 There is also an intensive review article on the temperature dependence of the Josephson maximum current for high-T c SNS junctions. 32 Although there exist several reports on the d-wave effect of the Josephson junctions, [33][34][35][36] no angle-resolved measurement of the junction properties seems to have been carried out. It has been reported that the bicrystal grain-boundary is natu-rally rough due to the original crystal defects of the substrate which will remarkably affect the d-wave properties of the junction.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea here is to exploit d-wave Josephson junctions, exhibiting a degenerate ground state and a p-periodic current-phase relationship. However inhomogeneous nature of in-plane d-wave Josephson junctions [2] as well as a weak nonlinearity for these junctions in the c-direction [3] makes a qubit realization almost impossible. Another proposal was to implement qubit which consists of a loop with three (or more) small-capacitance conventional Josephson junctions.…”
Section: Introductionmentioning
confidence: 99%